PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE MENCARI PASANGAN UNTUK MENINGKATKAN MOTIVASI BELAJAR PKN SISWA KELAS IV SD NEGERI 19 BATU BULEK KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR - Efriyeni Efriyeni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low motivation to learn Civics in the sixth grade students of SDN 19 Batu Bulek. This studyaims to improve students' learning motivation in Civics learning through a type of cooperative cooperative learning model inthe sixth grade students of SDN 19 Batu Bulek. The subjects of this study were all sixth grade students of SDN 19 Batu Bulek,totaling 18 people, 2017-2018 school year. The form of research is classroom action research. This research instrumentconsists of performance instruments and data collection instruments in the form of observation sheets of teacher activitiesand student activities. Based on the results of the analysis and discussion as stated it can be concluded that with theimplementation of cooperative learning models the type of finding a partner can increase civics learning motivation class IVSDN 19 Batu Bulek. In cycle I shows that student learning motivation is still relatively low with a score of 55 with an averagepercentage of 4 indicators of learning motivation at 76.4%. whereas in the second cycle reached a score of 67 with very highcriteria, with an average student learning motivation for learning motivation indicators (4 indicators) of 93.1%. This is dueto the application It is known that the type of finding a partner in principle is a cooperative learning model that can evoke thespirit of student learning, because the cooperative learning model of finding a partner in its application will make theclassroom atmosphere more active and make students try to find answers to a problem in a material with it. Activities in classlike this will increase student motivation in learning Civics.